Efficacy of PGF2α, Calcium, Phosphorus, Oxytetracycline and Meloxicam on Fetal Membrane Retention and Postpartum Ovarian Activity in Buffaloes - Indurkar, Sandeep; Tiwari, Rajendra Prasad; Mishra, Girish Kumar; Dubey, Meenu (The Indian Journal of Animal Reproduction, 2022)
Present study was conducted on buffaloes (n=24) which were classified into two groups. In group I, 12 buffaloes after normal calving were randomly classified in treatment (n=6) and control (n=6) sub groups. Whereas in group II, 12 buffaloes after normal calving  having  RFM/ROP 12 hours after calving were randomly classified in treatment  (n=6) and control (n=6) sub groups. In group I and II , the buffaloes in treatment group were administered Dinoprost (25 mg); Meloxicam @0.5 mg/kg body wt., Oxytetracycline @5 mg/kg body wt. i/m and calcium i/v immediately after and after 12 hours of calving, respectively. However, the buffaloes in control group were not given any treatment.There was lower incidence of RFM (16.66% vs 50.00%; P0.05), early disappearance of fetid discharge (1.83±0.10 vs 2.66±0.33 days; P>0.05), early disappearance of muco-purulent discharge (3.25±0.65 vs 4.66±0.61 days; P>0.05), early uterine involution (32.83±4.43 vs 36.00±6.91 days, P
Keywords: Buffalo; Postpartum; Prostaglandin analogue; Retention of placenta